The Path to and Lessons from the Economic Crisis in Estonia: Employee Compensation Development - Reiljan, Janno (Estonian Discussions on Economic Policy, 2013)
The aim of this article is to describe Estonia’s economic development strategy in the Baltic Sea region primarily from the perspective of labour costs as a factor in international competitiveness. Estonia’s position in the international division of economic activities will be explored based on expert assessments in the context of a study of theoretical literature about labour compensation as a factor in international competitiveness. The differences between the impact of the economic boom and crisis periods on the level and dynamics of employee compensation (labour related expenditures), and gross and net salary in Estonia at the national level will be empirically analysed. An empirical analysis will also be performed to describe the changes in the structure of economic activities (NACE-classification) in Estonia